1998
DOI: 10.1046/j.1432-1327.1998.2520591.x
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate‐cyclase‐inhibitory protein is a frog retinal Ca2+‐binding protein related to mammalian guanylate‐cyclase‐activating proteins

Abstract: Two guanylate-cyclase-activating proteins (GCAP) encoded by a tail-to-tail gene array have been characterized in the mammalian retina. Using frog retina as a model, we obtained evidence for the presence of a photoreceptor Ca 2ϩ -binding protein closely related to GCAP. This protein (206 amino acids) does not stimulate guanylate cyclase (GC) in low [Ca 2ϩ ], but inhibits GC in high [Ca 2ϩ ], and is therefore termed guanylate-cyclase-inhibitory protein (GCIP). Sequence analysis indicates that GCIP and GCAP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…3A). These results suggest that GCAP1 and GCAP2 entirely account for Ca 2ϩ regulation of GC in mouse retinas, and that other recently characterized GC-regulatory proteins, such as GCIP in frog (27) and GCAP3 in higher vertebrates (10), are not expressed or cannot compensate for the absence of GCAP1 and GCAP2 in mouse photoreceptors.…”
Section: Gcap2 Expression In Gcaps ؊͞؊mentioning
confidence: 59%
“…3A). These results suggest that GCAP1 and GCAP2 entirely account for Ca 2ϩ regulation of GC in mouse retinas, and that other recently characterized GC-regulatory proteins, such as GCIP in frog (27) and GCAP3 in higher vertebrates (10), are not expressed or cannot compensate for the absence of GCAP1 and GCAP2 in mouse photoreceptors.…”
Section: Gcap2 Expression In Gcaps ؊͞؊mentioning
confidence: 59%
“…1 and 3-7). These observations exclude the possibility that inhibitory regulators, such as guanylyl cyclaseinhibitory protein (40) and RGS9 (41), are complexed with retGC-1 to form the 210-kDa product. Using a RGS9-specific antibody (41) we have shown that RGS9 is not involved in the 210-kDa product (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, it is believed that S100 proteins are not involved in phototransduction. Additional mechanisms and factors may also be involved in the regulation of retGCs, including phosphorylation (34,35), ATP binding (36 -38), actin binding (39), an inhibitor (guanylyl cyclase-inhibitory protein) of GCAP-activated retGC in amphibian retina (40), and inhibition of retGC-1 by RGS9 (41).…”
mentioning
confidence: 99%
“…We note that the inhibitory activity was coeluted with GCBP-55 from both the immunoaffinity and the ion exchange (Econo S) columns. GCBP-55 is not the GC inhibitor reported recently (14), because amino acid sequences in these proteins are completely different, as described below.…”
Section: Interaction Of Rgs9 With Guanylyl Cyclase 22170mentioning
confidence: 92%
“…Activation of GC by Ca 2ϩ /GCAPs has been established (11-13); however, a protein inhibitor on GC activity has also been isolated from amphibian photoreceptors (14). Moreover, GC isoforms (10,(15)(16)(17)(18) as well as GC phosphorylation (19,20) have been described, although the physiological significance of this GC diversity is unknown.…”
mentioning
confidence: 99%